ANALISIS RESPON SISWA TERHADAP MATA PELAJARAN MATEMATIKA PADA MATERI PECAHAN SENILAI DENGAN KARTU DOMINO BERBANTUAN VISUAL BASIC APPLICATION FOR EXCEL - Agus Sunandar; Yana Pirmanto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research was conducted to determine students' responses to mathematics learning on fractions with the value of domino cards assisted by Visual Basic Application for Excel. This research uses descriptive qualitative. The sample for this study were 20 students of SMPN 1 Ciranjang. The instrument in this study used a closed questionnaire containing 20 items of student response statements to learning material worth fractions assisted by domino card learning media based on Visual Basic Application for Excel. The results of this study indicate that the students' responses to mathematics learning on fractions with the value of domino cards assisted by Visual Basic Application for Excel are classified as positive. This is evident from the overall average percentage of 79% which is classified as strong.